Methane emissions respond to soil temperature in convergent patterns but divergent sensitivities across wetlands along altitude. (12th December 2020) - Zhu, Dan; Wu, Ning; Bhattarai, Nabin; Oli, Krishna Prasad; Chen, Huai; Rawat, Gopal Singh; Rashid, Irfan; Dhakal, Maheshwar; Joshi, Srijana; Tian, Jianqing; Zhu, Qiu'an; Chaudhary, Sunita; et al.
Abstract: Among the global coordinated patterns in soil temperature and methane emission from wetlands, a declining trend of optimal soil temperature for methane emissions from low to high latitudes has been witnessed, while the corresponding trend along the altitudinal gradient has not yet been investigated. We therefore selected two natural wetlands located at contrasting climatic zones from foothill and mountainside of Nepal Himalayas, to test: (1) whether the optimal temperature for methane emissions decreases from low to high altitude, and (2) whether there is a difference in temperature sensitivity of methane emissions from those wetlands. We found significant spatial and temporal variation of methane emissions between the two wetlands and seasons. Soil temperature was the dominant driver for seasonal variation in methane emissions from both wetlands, though its effect was perplexed by the level of standing water, aquatic plants, and dissolved organic carbon, particularly in the deep water area. When integrative comparison was conducted by adding the existing data from wetlands of diverse altitudes, and the latitude‐for‐altitude effect was taken into account, we found the baseline soil temperatures decrease whilst the altitude rises with respect to a rapid increase in methane emission from all wetlands, however, remarkably higher sensitivity of methane emissions to soil temperature (apparent Q 10 ) was found in mid‐altitude wetland. We provide the first evidence of an apparent decline in optimal temperature for methane emissions with increasing elevation. These findings suggest a convergent pattern of methane emissions with respect to seasonal temperature shifts from wetlands along altitudinal gradient, while a divergent pattern in temperature sensitivities exhibits a single peak in mid‐altitude. Abstract : Temperature has been widely recognized as the most fundamental factor among a myriad of variables regulating methane emissions from wetlands. This study provides the first evidence of an apparent decline in optimal temperature for methane emissions with increasing elevation, and suggests a convergent pattern of methane emissions with respect to seasonal temperature shifts along altitudinal gradient, while a divergent pattern in temperature sensitivities exhibits a remarkable peak in mid‐altitude.